2016
DOI: 10.1007/s10461-016-1612-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians’ Willingness to Prescribe HIV Pre-exposure Prophylaxis for People who Inject Drugs

Abstract: Pre-exposure prophylaxis for HIV (PrEP) is recommended for people who inject drugs (PWID). Despite their central role in disease prevention, willingness to prescribe PrEP to PWID among primary care physicians (PCPs) is largely understudied. We conducted an online survey (April – May 2015) of members of a society for academic general internists regarding PrEP. Among 250 respondents, 74% (n=185) of PCPs reported high willingness to prescribe PrEP to PWID. PCPs were more likely to report high willingness to presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 31 publications
0
55
1
Order By: Relevance
“…Several papers focused on transgender women [ 49 , 53 , 62 ], Black and Latina women [ 48 ], Black and Latino MSM [ 51 ], adolescents [ 65 , 66 ], men who engage in street-based sex work [ 46 ], heterosexual couples [ 69 ], and people who inject drugs [ 43 , 63 ]. These papers point to stigma associated with PrEP use and the intersection of HIV-stigma with transphobia and homophobia [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several papers focused on transgender women [ 49 , 53 , 62 ], Black and Latina women [ 48 ], Black and Latino MSM [ 51 ], adolescents [ 65 , 66 ], men who engage in street-based sex work [ 46 ], heterosexual couples [ 69 ], and people who inject drugs [ 43 , 63 ]. These papers point to stigma associated with PrEP use and the intersection of HIV-stigma with transphobia and homophobia [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another theme we identified in the literature was the belief that being on PrEP would cause individuals to engage in more ''risky'' behavior, such as having sex without a condom or not inquiring about STIs before engaging in sexual activity. 25,[27][28][29]33,34,36,37,39,42,43,45,49,50 Although in most studies worries about risk compensation were minimal, it did emerge as a common theme across the reviewed literature. Specifically, 26% of Washington State providers believed that being on PrEP could increase engagement in risky sexual behavior.…”
Section: Concerns About Behavioral and Health Consequencesmentioning
confidence: 99%
“…36,37 Some providers even stated that higher-risk individuals would be better off using condoms instead of PrEP. 33 Another study found that fears of risk compensation were more prominent in providers with little PrEP prescribing experience. 27 In addition to concerns about risk compensation, providers in another reviewed study worried about HIV resistance caused by PrEP, cited minimal concerns about side effects, but recognized the importance of monitoring patients to minimize risks.…”
Section: Concerns About Behavioral and Health Consequencesmentioning
confidence: 99%
“…PrEP uptake may also be insufficient in people who inject drugs (PWID). A survey of primary care physicians showed over one-quarter had low willingness to prescribe PrEP to PWID, despite some PWIDs having a substantial risk for HIV acquisition [9]. Cisgender women at risk of HIV also have relatively low PrEP uptake.…”
Section: Introductionmentioning
confidence: 99%